Indonesia : Staff Report for the 2005 Article IV Consultation and Third Post-Program Monitoring Discussions Supplementary Information. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents Indonesia's 2005 Article IV Consultation and Third Post-Program Monitoring discussions. The economic strategy has produced positive results over time. Economic growth has gained momentum year by year, inflation has been substantially reduced, and the external position has remained sound. In spite of these achievements, considering Indonesia's widespread poverty and unemployment, the key policy challenge is to further deepen the reforms to place the economy on an even higher growth path.